Results of the Water Quality Study Within the Luga-Balt-2 International Project - Tuija Ranta-Korhonen; M. V. Markova; E. V. Vasilev; A. S. Ogluzdin; N. S. Vasileva (Сельскохозяйственные машины и технологии)
The authors noted the transboundary nature of anthropogenic impact on the environment, including that on water bodies, which needs to be studied in an international format. (Research purpose) To determine the water state of the Urpolanjoki River in the Mikkeli area in Finland and the Luga River in Russia in order to prepare proposals for improvement. (Materials and methods) Water quality was specified by 11 parameters by sampling and analyzing them in the laboratory. Additionally, 1South-Eastern Finland University of Applied Sciences carried out online monitoring using the YSI 6920-V2 continuous water probe. The authors used standard methods of processing statistical, field data. (Results and discussion) The authors revealed good, stable during the entire monitoring period, water quality in the Urpolanjoki River. The authors showed that the water quality in the Luga River deteriorates downstream, in particular, due to the agricultural and livestock farms’ activities near the river basin. Thus, the Kjeldahl nitrogen and total phosphorus content at the upstream point is 10.8 milligrams and 119 micrograms per liter, respectively, and at the downstream point, it is only 1.6 milligrams and 28 micrograms, respectively. (Conclusions) It was determined that the analyzed indicators correspond to the category of good quality: the level of water oxygen saturation fluctuated within 88.76-117.83 per cent during the monitoring period; the color was 30 milligrams per liter on the platinum-cobalt scale, which means a low humus content in the water; the presence of solids in the water ranged from 1.1 to 2.4 milligrams per liter; the total phosphorus content in water is below 9.2 micrograms per liter, that is, within the normal limits. During the monitoring of the Luga River, a clear influence of nearby agricultural enterprises and settlements was detected.